ENTERTAINMENT VIOLENCE IN THE LEISURE OF STUDENT YOUTHS - M. I. Zhabskiy; К. A. Tarasov (Высшее образование в России)
The current bursts of violence in the Russian comprehensive school actualize the issues of the place held by entertainment violence in the cinematic leisure of the learning youth, and of the possibility of its stimulating the aggressive behavior in their midst. Based on the proceedings of a sociological survey in cinema auditoria of the Russian heartland, it has been shown that films with scenes of violence in them form, at a minimum, half of the individual theatrical repertoire for every third pupil and student of both trade schools and institutions of higher education. From a psychological standpoint, the habitualization of «the aggressive film diet» is conditioned, in part, by the action of such mechanisms of spontaneous spectator immersion in the film’s world as empathy and identification. Accruing some sort of magic under their influence, the spectacle of violence deforms the spectator identity among a certain part of students which is fraught with dysfunctional social consequences. The authors propose a complex approach to the solution of the problem which integrates the socializing capabilities of media education and the family, while the legal regulation is augmented by self-regulation from cinema bodies.